DEMOKRASI POST-PENYIARAN DALAM MUNCULNYA FANS POLITIK DI INDONESIA - Vannyora Okditazeini (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This study aims to elaborate on how the pattern of democracy shifts along with the development of technology and communication. This shift can be seen from the use of broadcast media as a channel of aspirations to the use of new media known as post-broadcasting democracy. This post-broadcasting democratic pattern will be seen on the #2019gantippresi fanpage community and will analyze the activities carried out by members in the group. This paper is a netnographic study by integrating the concepts of mediated politics, post-broadcasting democracy, and political fans. The results of the study show that this shift in the pattern of democracy creates a new phenomenon, namely political fans. This can be seen in: first, the activities carried out by political fans on social media foster a political constellation with high mobility. Second, post-broadcasting democratic publics become interactive publics. Third, political fans produce texts which in turn become cultural productions in mediated politics. Fourth, the activities of these political fans indirectly influence public opinion regarding the political actors they admire. The author observes that the phenomenon of political fans as seen on the #2019gantippresi fanspage can be a new strategy for political actors in growing fanatical sympathizers by utilizing technological and communication developments.